Friction aided deep drawing using newly developed blank-holder divided into eight segments - Hassan, M.A.; Takakura, N.; Yamaguchi, K. (2003)
A new process on friction aided deep drawing has been developed in which a metal blank-holder divided into eight fan-shaped segments is used instead of an elastomer ring used in the Maslennikov process. This blank holding device consists of four drawing segments and four small wedges, which can move radially in- and out-wards under a certain blank-holding pressure. The drawing process can be efficiently performed using an assistant punch, which partially supports the deformation of the blank as well as improving the shape, and dimensional accuracy of the drawn cup. Deep drawing experiments have been done using soft aluminum sheets of 0.5 and 1.0 mm in thickness to understand the main features of the proposed drawing process. Theoretical analyses based on the energy and slab methods have also been conducted to study the effect of main process parameters on the minimum blank holding pressure required for the onset of deformation, and to obtain the other optimum working conditions. The possibility of the new process has been confirmed by producing deep and successful cups with a drawing ratio of 4.0, although the number of drawing operations is still high. (C) 2003 Elsevier Science Ltd. All rights reserved.